Performance Expectations for IT Graduates in Software Development (Global Journal of Computer Science and Technology, 2019)
Technology makes the world more connected than it did yesterday, and it integrates worldwide activities in a blink of an eye. In the IT sector, there are several job roles as identified under software development. These job roles have different duties and tasks which requires employees, with a unique set of skills to match the specific requirements in the field. During the past few decades, the employment landscape has changed, and new occupations are rising in the field of software development, yet no satisfactory evidence has been provided by existing literature on the performance expectations in the industry, for IT graduates in software development, in the Sri Lankan context. Therefore, this research objectives to ascertain the expectations of employers on the technical, personal, educational, and general competencies of employees, holding an IT degree and to draw differences among individual and teamwork settings according to the identified competencies.
Keywords: competencies; IT graduates; IT professionals; software development industry; work expectations